New Pyrrole-Chalcone Hybrids Against Acetylcholinesterase: Synthesis, In Vitro, and Computational Studies - Ridwanuloh, Dadan; Danova, Ade; Hermawati, Elvira; Chavasiri, Warinthorn; Ihsanawati, Ihsanawati; Alni, Anita (Pandawa Institute, 2026)
Acetylcholinesterase (AChE) inhibition remains a central therapeutic approach for Alzheimer’s disease (AD), as it helps preserve synaptic acetylcholine levels, enhances cholinergic neurotransmission, and mitigates early cognitive decline. In this study, eight novel pyrrole–chalcone hybrids (3–10), consisting of four pyrrole–chalcones (3–6) and four pyrrole–chalcone amides (7–10), were designed, synthesized, and biologically evaluated for AChE inhibition. Among them, compound 8 (N-(4-methoxybenzyl)-pyrrole–chalcone amide) and compound 10 (N-(3,4-dimethoxybenzyl)-pyrrole–chalcone amide) demonstrated the strongest inhibitory activity, with IC₅₀ values of 3.1 and 2.8 µM, respectively, comparable to galantamine. Kinetic assays confirmed that both compounds act as noncompetitive inhibitors, as indicated by reduced Vmax without significant alteration in Km, while compound 10 exhibited Ki of 0.8 µM, reflecting high enzyme affinity. Molecular docking revealed strong binding interactions of compounds 8 and 10 with key AChE residues (Trp84, Phe330, Tyr334), supported by π–π stacking, π–alkyl interactions, and hydrogen bonding, with binding energies of –9.2 (compound 8) and –8.9 kcal/mol (compound 10). Molecular dynamics simulations further demonstrated that compound 10 forms a more stable and compact complex with AChE, as indicated by consistent RMSD values and a stable radius of gyration. SwissADME analysis confirmed favorable pharmacokinetic profiles for both ligands, including Lipinski compliance, high GI absorption, and absence of PAINS alerts, despite the lack of predicted BBB permeability. Overall, compound 10 emerges as the most promising noncompetitive AChE inhibitor in this series, exhibiting strong binding affinity, structural stability, and drug-likeness, thus warranting further optimization and in vivo evaluation.